Empowering hypoxia to convert cold tumors into hot tumors for breast cancer immunotherapy - Lu Liu; Danping Wu; Zhiwen Qian; Ying Jiang; Yilan You; YiDa Wang; Feng Zhang; Xin Ning; Jie Mei; Jabed Iqbal; Yanfang Gu; Yan Zhang (Cell Death Discovery)
Abstract Breast cancer remains the most common cancer among women globally and a leading cause of cancer-related death. Despite the promise of immunotherapy for triple-negative breast cancer (TNBC), its overall effectiveness is hindered by the cold tumor microenvironment (TME), characterized by sparse immune cell infiltration. This review explores the pivotal role of hypoxia in shaping the breast cancer TME and its influence on immunotherapy efficacy. As a defining feature of most solid tumors, including breast cancer, hypoxia drives aggressive tumor behavior, metastasis, and treatment resistance. The hypoxic TME promotes immune evasion and maintains the cold tumor phenotype. Targeting hypoxia offers a potential strategy for transforming cold breast tumors into hot tumors that respond more effectively to immunotherapy. This review consolidates existing insights into the interplay between hypoxia, tumor immunophenotypes, and immunotherapy in breast cancer. By analyzing the mechanisms through which hypoxia modulates the TME and immune response, it proposes innovative strategies to enhance immunotherapy outcomes. This comprehensive analysis lays the groundwork for developing more effective combination therapies to improve breast cancer prognosis.